Protective effect of L-carnitine on alcoholic fatty liver in rats - Bahçecioglu, IH; Demir, A; Üstündag, B; Ilhan, M; Baydas, G; Canatan, H; Ozercan, I (Lippincott Williams & Wilkins, 1999)
We have investigated the protective effects of L-carnitine against experimental alcoholic fatty liver in terms of steatosis, liver damage, lipid peroxidation and lipid levels. 36 male Wistar rats were divided into three groups. One group received a liquid diet and the other two the liquid diet supplemented with ethanol for 6 weeks. One of the groups given alcohol also received L-carnitine (250 mg/kg, i.m., 3 times/week) and the other isotonic saline (i.m., 3 times/week) as placebo. All of the rats given alcohol developed fatty liver, presenting different grades at the end of the 6 weeks. The levels of steatosis, inflammation and necrosis in the livers of alcohol + L-carnitine animals were significantly lower (P < 0.001) compared to the alcohol + saline animals' livers. The levels of tissue malondialdehyde (MDA) in the liver and plasma were significantly lower in the L-carnitine + alcohol group (P < 0.001) than in the saline + alcohol group. Moreover, the activity of alanine aminotransferase (ALT) and levels of triglycerides and LDL-cholesterol were significantly lower in the L-carnitine + alcohol group (P < 0.05, P < 0.01 and P < 0.01, respectively) compared to the alcohol + saline group. Based on these results, it is possible to postulate that L-carnitine may have a preventive role against alcohol-induced steatosis and liver damage. Med Sci Res 27:475-478 (C) 1999 Lippincott Williams & Wilkins.
Keywords: alcoholic fatty liver; L-carnitine; liver damage